1999
DOI: 10.1101/gad.13.22.2983
|View full text |Cite
|
Sign up to set email alerts
|

Gata5 is required for the development of the heart and endoderm in zebrafish

Abstract: The mechanisms regulating vertebrate heart and endoderm development have recently become the focus of intense study. Here we present evidence from both loss-and gain-of-function experiments that the zinc finger transcription factor Gata5 is an essential regulator of multiple aspects of heart and endoderm development. We demonstrate that zebrafish Gata5 is encoded by the faust locus. Analysis of faust mutants indicates that early in embryogenesis Gata5 is required for the production of normal numbers of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
345
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 402 publications
(371 citation statements)
references
References 58 publications
21
345
0
5
Order By: Relevance
“…Knockout and overexpression experiments have revealed important roles for GATA5 during Zebrafish cardiogenesis (Reiter et al, 1999), but not in mouse as suggested by the GATA5 mutant mice (Molkentin et al, 2000). Furthermore, initial analysis of GATA5 function in Xenopus using a translation-blocking MO (tlMO) had suggested no role in cardiogenesis (Peterkin et al, 2007), which, however, was called into question in a recent study that used a newly designed splice-blocking MO (spMO) (Haworth et al, 2008) to suggest an important role for Xenopus GATA5 during early embryogenesis.…”
Section: Redundancy and Functional Differences Between Gata Factors Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockout and overexpression experiments have revealed important roles for GATA5 during Zebrafish cardiogenesis (Reiter et al, 1999), but not in mouse as suggested by the GATA5 mutant mice (Molkentin et al, 2000). Furthermore, initial analysis of GATA5 function in Xenopus using a translation-blocking MO (tlMO) had suggested no role in cardiogenesis (Peterkin et al, 2007), which, however, was called into question in a recent study that used a newly designed splice-blocking MO (spMO) (Haworth et al, 2008) to suggest an important role for Xenopus GATA5 during early embryogenesis.…”
Section: Redundancy and Functional Differences Between Gata Factors Dmentioning
confidence: 99%
“…In contrast to zebrafish where a critical role for GATA5 in specification of the myocardium was demonstrated (Reiter et al, 1999), gene knockout studies in mice suggested that GATA5 was dispensable for embryonic development (Molkentin et al, 2000). These mouse findings seemed to be supported by initial Xenopus studies reporting only a minor role for GATA5 in heart formation (Peterkin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, most, but not all, of the nkx2.5-expressing cells terminally differentiate into myocardiocytes (Serbedzija et al, 1998;. Differentiating myocardiocytes initiate expression of genes that encode cardiac sarcomere proteins, such as cmlc1 and cmlc2 (Reiter et al, 1999;Yelon et al, 1999) (Fig. 2).…”
Section: Specification and Differentiation Of The Zebrafish Myocardiummentioning
confidence: 99%
“…The transcription factor gene gata5 is expressed in a broad region of the ALPM, including the portion that expresses nkx2.5 (Reiter et al, 1999). Mutation of the faust/gata5 locus results in a dramatic reduction of nkx2.5 expression (Reiter et al, 1999).…”
Section: Which Factors Induce Nkx25 Expression?mentioning
confidence: 99%